Transcriptomic and epigenetic analysis of breast cancer stem cells. (26th February 2018) - Li, Guochao; Wang, Dong; Ma, Wencui; An, Ke; Liu, Zongzhi; Wang, Xinyu; Yang, Caiyun; Du, Fengxia; Han, Xiao; Chang, Shuang; Yu, Hui; Zhang, Zilong; et al.
Aim: Cancer stem cells (CSCs) drive triple-negative breast cancer recurrence via their properties of self-renewal, invasiveness and radio/chemotherapy resistance. This study examined how CSCs might sustain these properties.Materials & methods: Transcriptomes, DNA methylomes and histone modifications were compared between CSCs and non CSCs.Results: Transcriptome analysis revealed several pathways that were activated in CSCs, whereas cell cycle regulation pathways were inhibited. Cell development and signaling genes were differentially methylated, with histone methylation analysis suggesting distinct H3K4me2 and H3K27me3 enrichment profiles. An integrated analysis revealed several tumor suppressor genes downregulated in CSCs.Conclusion: Differential activation of various signaling pathways and genes contributes to the tumor-promoting properties of CSCs. Therapeutic targets identified in the analysis may contribute to improving treatment options for patients.